Acrylic Polymers in Healthcare - Reddy, Boreddy S.R (IntechOpen, 2017)
This book on Acrylic Polymers for Healthcare presents eight chapters organised into three parts by providing new ideas in design, synthesis and a detailed study of new acrylate materials in healthcare applications. Part I represents Chapters 1, 2, 3 and 4 focussing on toning up of technologies for making dental dentures with better properties. Part II comprises Chapters 5 and 6 dealing with synthetic polymer-based nanoparticles as intelligent drug delivery systems and bismuth nanoparticles for improved green light emission. Part III represents Chapters 7 and 8 describing the aspects of mitigation of acrylamide in foods in the context of an African perspective and the importance of acrylic-based polymeric adsorbents so that the reader can get an idea about the various types and forms of polymeric materials used for the removal of heavy metals from water.